Virtual Reality Cerebral Aneurysm Clipping Simulation With Real-Time Haptic Feedback. Issue 2 (March 2015) - Alaraj, Ali; Luciano, Cristian J.; Bailey, Daniel P.; Elsenousi, Abdussalam; Roitberg, Ben Z.; Bernardo, Antonio; Banerjee, P. Pat; Charbel, Fady T.
Abstract : BACKGROUND: With the decrease in the number of cerebral aneurysms treated surgically and the increase of complexity of those treated surgically, there is a need for simulation-based tools to teach future neurosurgeons the operative techniques of aneurysm clipping. OBJECTIVE: To develop and evaluate the usefulness of a new haptic-based virtual reality simulator in the training of neurosurgical residents. METHODS: A real-time sensory haptic feedback virtual reality aneurysm clipping simulator was developed using the ImmersiveTouch platform. A prototype middle cerebral artery aneurysm simulation was created from a computed tomographic angiogram. Aneurysm and vessel volume deformation and haptic feedback are provided in a 3-dimensional immersive virtual reality environment. Intraoperative aneurysm rupture was also simulated. Seventeen neurosurgery residents from 3 residency programs tested the simulator and provided feedback on its usefulness and resemblance to real aneurysm clipping surgery. RESULTS: Residents thought that the simulation would be useful in preparing for real-life surgery. About two-thirds of the residents thought that the 3-dimensional immersive anatomic details provided a close resemblance to real operative anatomy and accurate guidance for deciding surgical approaches. They thought the simulation was useful for preoperative surgical rehearsal and neurosurgical training. A third of the residents thought that the technology in its current form provided realistic haptic feedback for aneurysm surgery. CONCLUSION: Neurosurgical residents thought that the novel immersive VR simulator is helpful in their training, especially because they do not get a chance to perform aneurysm clippings until late in their residency programs. Abstract : Supplemental Digital Content is Available in the Text.